Pembrolizumab in a Patient With Heavily Pre-Treated Squamous Cell Thymic Carcinoma and Cardiac Impairment: A Case Report and Literature Review - Cafaro, Alessandro; Bongiovanni, Alberto; Di Iorio, Valentina; Oboldi, Devil; Masini, Carla; Ibrahim, Toni (Frontiers in Oncology, 2020)
Immunotherapy directed at the programmed cell death-1 receptor (PD-1) or its ligand PD-L1 has proven effective in solid malignancies such as melanoma, non-small cell lung cancer (NSCLC), urothelial cancer, renal cell carcinoma, and head and neck cancer. Compared with cytotoxic chemotherapy, radiotherapy or molecular targeted agents, immunotherapy is an innovative strategy for treating malignancies, with durable clinical responses and manageable adverse events. Thymic carcinomas are extremely rare, constituting only 0.06% of all malignancies, and can be distinguished from benign thymomas by their aggressive nature and poor prognosis. National Comprehensive Cancer Network guidelines recommend resection followed by adjuvant platinum-based chemotherapy for resectable tumours. However, the results for metastatic or relapsed thymic carcinoma are unsatisfactory, with no regimen showing a consistent benefit. Moreover, the rarity of these tumours makes it difficult to carry out clinical trials. Herein we report a remarkable result obtained from the use of immunotherapy with pembrolizumab in a case of heavily pre-treated squamous cell thymic carcinoma and cardiac impairment. We also include a literature review of clinical trials on anti PD-1/PD-L1 drugs for the treatment of thymic epithelial cancers, taking a close look at cardiac toxicity.